A structural model of the relationship between personality traits and self-esteem with academic self-efficacy with the mediation of students' achievement motivation - Salman Akbardoost zanganeh; Ata Tehranchi; Zahra Ejadi (مطالعات روانشناسی تربیتی)
The aim of the current research was to explain the structural model of the relationship between personality traits and self-worth with academic self-efficacy through the mediation of students' motivation to progress. In a structural equation and correlation design, 306 male students of the second secondary school in Gonabad city were selected in the academic year of 2021-2022 with a multi-stage cluster random sampling method, and the questionnaires of Neo's personality traits (1985), self-esteem questionnaires of Kroker et al. (2003) , Morgan and Jinks' (1999) academic self-efficacy and Hermans' (1977) achievement motivation completed. Data analysis was done with Pearson correlation and structural equation modeling with SPSS.27 and AMOS.24 software. The hypothesized model had a good fit with the data. The results showed that personality traits and self-esteem have a significant direct and indirect effect on academic self-efficacy (P≥0.01). And the direct effect of these variables on academic self-efficacy is more than its indirect effect. Also, the comparison of direct and indirect effects shows that motivation to progress in relation to personality traits and self-worth plays a mediating role with academic self-efficacy, and self-worth (P<0.01) compared to personality traits ( P>0.05) has a greater indirect effect on academic self-efficacy. Based on this, it can be concluded that students' academic self-efficacy can be increased due to the relationship between personality traits and self-worth with the motivation to progress, and by strengthening the motivation to progress, the relationship between personality traits and self-worth can be strengthened with students' academic self-efficacy.